(untitled) (Malaysian Journal of Learning and Instruction, 2024)
Purpose – Although there exists a substantial body of research discussing the efficient implementation of classroom-based assessment (CBA), there is a dearth of knowledge regarding its application within the context of English as a Second Language (ESL) education in Malaysia. The current study aimed to investigate the ESL teachers’ practices in implementing CBA, with a specific emphasis on the alignment of their assessment procedures with the policy requirements. Methodology – Hence, this research utilizes a qualitative approach, employing data triangulation through semi-structured interviews, classroom observations, and document analysis. Four ESL teachers from two public secondary schools in the northeast district of the Malaysian city of Pulau Pinang were selected to participate in the study. The four ESL teachers taught the same grade (Form 2) at the secondary level. The data collected were analyzed through thematic analysis procedures. Findings – This research discovered that teachers demonstrate commendable practices in planning the CBA. They exhibited discernment by formulating instructional objectives in line with the curriculum document. However, a misalignment was observed in teachers’ practices during the implementation phase. Despite employing various assessment methods, teachers predominantly leaned towards formal assessments, with less emphasis on studentcentred approaches. Challenges surfaced when explicit learning objectives were not effectively communicated, and the use of standardized rubrics, was not tailored to students’ diverse capabilities. At the reporting phase, concerns were raised about an excessive focus on administrative data recording. This study brought to light that teachers relied on the accumulation of students’ grades and marks to determine the mastery levels, thus corroborating with the examoriented practices. Significance – This study holds significant value for the field of ESL education in Malaysia by shedding light on the actual implementation of CBA and its alignment with policy directives. By providing information on how policies are implemented at the local level, contributes to the improvement of assessment policies that can be tailored to classroom realities.